2015
DOI: 10.1002/2015jd023181
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and diurnal features of amine‐enhanced boundary layer nucleation

Abstract: Amines have recently been found to be an important ingredient in the nucleation and initial growth of atmospheric aerosols; however, global estimates of the spatial and temporal extent of amine‐enhanced nucleation are currently missing. We utilize two recently published laboratory data sets of amine‐sulfuric acid nucleation to evaluate the accuracy of previously published nucleation parameterizations and to produce a new amine‐enhanced new particle formation (NPF) parameterization that better reproduces the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 144 publications
1
50
0
Order By: Relevance
“…To summarize, dimethylamine has hitherto been the most studied atmospheric amine. While other similar amine species have been assumed to have comparable average properties with respect to clustering [e.g., Loukonen et al, 2010;Bergman et al, 2015], both experimental [Jen et al, 2014;Glasoe et al, 2015] and theoretical [Kurtén et al, 2008;Paasonen et al, 2012] studies suggest that there may be differences between the stabilization potentials of different alkylamines at least for the smallest clusters. Systematic comparisons of different amine species are scarce, but they are needed to assess how to treat this complex array of species in atmospheric models.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, dimethylamine has hitherto been the most studied atmospheric amine. While other similar amine species have been assumed to have comparable average properties with respect to clustering [e.g., Loukonen et al, 2010;Bergman et al, 2015], both experimental [Jen et al, 2014;Glasoe et al, 2015] and theoretical [Kurtén et al, 2008;Paasonen et al, 2012] studies suggest that there may be differences between the stabilization potentials of different alkylamines at least for the smallest clusters. Systematic comparisons of different amine species are scarce, but they are needed to assess how to treat this complex array of species in atmospheric models.…”
Section: Introductionmentioning
confidence: 99%
“…It is further known that marine biota also release certain gasphase amines, such as trimethylamine (TMA), into the atmosphere (e.g., Ge et al, 2011a;Van Neste et al, 1987;Gibb et al, 1999;Facchini et al, 2008), which subsequently may contribute to aerosol chemistry. Numerous chamber, modeling and field studies at southern latitudes (e.g., Almeida et al, 2013;Kürten et al, 2017;You et al, 2014;Bergman et al, 2015;Müller et al, 2009) have focused on sources, emission rates and gas-to-particle partitioning processes of atmospheric amines. So far, this research has shown that amines may take part in aerosol chemistry in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study has so far reported sulfuric acid-amine nucleation (Zhao et al, 2011) despite amine mixing ratios of up to tens of parts per trillion volume at some sites (Yu and Lee, 2012;You et al, 2014;Freshour et al, 2014;Yao et al, 2016). A global modeling study of sulfuric acid-amine nucleation has been carried out so far (Bergman et al, 2015), applying a nucleation parametrization based on the measurements of Almeida et al (2013) and Glasoe et al (2015).…”
mentioning
confidence: 99%